Ecotoxicoproteomic assessment of the functional alterations caused by chronic metallic exposures in gammarids. (June 2017) - Gismondi, E.; Thomé, J.-P.; Urien, N.; Uher, E.; Baiwir, D.; Mazzucchelli, G.; De Pauw, E.; Fechner, L.C.; Lebrun, J.D.
Abstract: Very few ecotoxicological studies have been performed on long-term exposure under controlled conditions, hence limiting the assessment of the impact of chronic and diffuse chemical pressures on the health of aquatic organisms. In this study, an ecotoxicoproteomic approach was used to assess the integrated response and possible acclimation mechanisms in Gammarus fossarum following chronic exposures to Cd, Cu or Pb, at environmentally realistic concentrations (i.e. 0.25, 1.5 and 5 μg/L respectively). After 10-week exposure, changes in protein expression were investigated in caeca of control and exposed males. Gel-free proteomic analyses allowed for the identification of 35 proteins involved in various biological functions, for which 23 were significantly deregulated by metal exposures. The protein deregulation profiles were specific to each metal, providing evidence for metal-specific action sites and responses of gammarids. Among the tested metals, Cu was the most toxic in terms of mortality, probably linked with persistent oxidative stress. Moulting and osmoregulation were the major biological functions affected by Cu in the long-term. In Pb-exposed gammarids, significant deregulations of proteins involved in immune response and cytoskeleton were observed. Reproduction appears to be strongly affected in gammarids chronically exposed to Cd or Pb. Besides, modified expressions of several proteins involved in energy transfer and metabolism highlighted important energetic reshuffling to cope with chronic metal exposures. These results support the fact that metallic pressures induce a functional and energetic cost for individuals of G. fossarum with potential repercussions on population dynamics. Furthermore, this ecotoxicoproteomic study offers promising lines of enquiry in the development of new biomarkers that could make evidence of long-term impacts of metals on the health of organisms. Graphical abstract: Highlights: Gammarids were chronically exposed to Cu, Cd and Pb under controlled conditions. Gel-free proteomic analyses were carried out in the caeca tissue of acclimated males. Acclimation has a functional and energetic cost for exposed individuals. Exposures generate changes in protein expression and associated biological functions. Some biological functions are metal-specifically affected in the long-term. Abstract : Establishing metal-specific profiles of protein deregulation makes evidence of functional alterations in gammarids chronically exposed to Cu, Cd or Pb .